Key Influencers of Satisfaction and Behavioral Intention of In-patients in Chengdu, China - Feng, Yuguo (Scholar: Human Sciences, 2023)
Purpose: Understanding the evaluation of hospital service quality by in-patients would improve the existing medical system’s results and service quality. Therefore, this study aims to evaluate key influencers of satisfaction and behavioral intention of In-patients in Chengdu, China. Research design, data, and methodology: The quantitative study emphasizes the data collection from 500 in-patients undergoing treatment in 20 public and private hospitals in Chengdu, China, in 2022. In addition, the sampling procedure of this study was divided into three steps: judgment sampling, quota sampling, and convenience sampling. Confirmatory factor analysis (CFA) was used to assess the convergent and discriminant validity of the measurement model, and the Structural equation model (SEM) was applied to test the effect of measured variables and conclude the research. Results: Patient satisfaction had a significant impact on behavioral intention. Moreover, reliability was the strongest factor that significantly impacted patient satisfaction, followed by tangibles, responsiveness, and image. However, empathy and assurance did not significantly impact patient satisfaction. Conclusions: There were many factors affecting patient satisfaction, involving hospitals, medical staff, patients themselves, and other aspects. Through the measurement and evaluation of patient satisfaction, the hospital can understand the expectations of in-patients and improve competitiveness.